Strategi Pengembangan Innovatif Untuk Mengatasi Kesulitan Belajar Peserta Didik Tunagrahita di SLBN Juwetkenongo Sidoarjo - Dimas Dzakiy Wahyu Pamungkas; Ardhea Dwi Ananda; Farrel Verlita Evelin; Azizatur Rohma; Kaniati Amalia (CV Putra Publisher, 2025)
This research explores strategies in the learning process of Tungrahita students holistically amidst individual developmental limitations that cause learning difficulties at SLBN Juwetkenongo. Despite facing the challenge of developmental limitations within themselves, the school has provided innovative and creative methods in the teaching and learning process to improve the success of their students. Using qualitative methods, including observations, interviews, documents with teachers, staff, and students, and analyzing documents, this research identifies the main innovation strategies implemented by the school. These include developing the independence of Tungrahita students, increasing self-confidence, optimizing available resources, peer influence, visualization learning, implementing collaborative and contextual learning processes. The findings highlight how learning methods can motivate students with special needs and ensure the growth of Tungrahita students to be more independent and actively socialize with others. Despite the progress, challenges such as limited teacher training, availability of resources and the role of parents still exist. As a result, valuable knowledge was gained about collaborative and effective school management practices that can be applied in schools with students with special needs